2015
DOI: 10.1021/acs.jpcc.5b00096
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulations of Quartz (101)–Water Interface over a Range of pH Values

Abstract: The original force field for clay materials (ClayFF) developed by Cygan et al. (J. Phys. Chem. B 2004, 108, 1255 is modified to describe negative charging of the (101) quartz surface above its point of zero charge (pH ≈ 2.0−4.5). The modified force field adopts the scaled natural bond orbital charges derived by the quantum mechanical calculations which are used to obtain the desired surface charge density and to determine the delocalization of the charge after deprotonation of surface silanol groups. Classica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
142
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(158 citation statements)
references
References 72 publications
10
142
1
Order By: Relevance
“…This conclusion is consistent with X-ray reflectivity studies, 48,49 optical measurements, 50,51 and recent molecular simulations. 47,52 One consequence of this observation is that the surface charge as determined from an AFM (or SFA) force measurement, which is based on the ion distribution in the diffuse layer, is always lower than the charge density determined by a titration measurement that measures the total number of protons or ions adsorbing to or desorbing from a surface. 53 As a final remark, Fig.…”
Section: Charge Regulation and Local Fluid Compositionmentioning
confidence: 99%
“…This conclusion is consistent with X-ray reflectivity studies, 48,49 optical measurements, 50,51 and recent molecular simulations. 47,52 One consequence of this observation is that the surface charge as determined from an AFM (or SFA) force measurement, which is based on the ion distribution in the diffuse layer, is always lower than the charge density determined by a titration measurement that measures the total number of protons or ions adsorbing to or desorbing from a surface. 53 As a final remark, Fig.…”
Section: Charge Regulation and Local Fluid Compositionmentioning
confidence: 99%
“…At the natural pH of 6.2 used here, the charge density of silica was ca. −0.03 C/m 2 (value taken from Kroutil et al [37] and supported by Goloub et al [38]). Metal cations, when present, acted as counterions on the silica, adsorbing on the negative sites that dominated the surface.…”
Section: Zeta Potential and Cation Adsorptionmentioning
confidence: 69%
“…The pzc can control sorption of protons and hydroxyl groups, which depends on the acid-base properties of the surface (Pecenyuk 1999). Previous studies reported that the pzc for the PA components were 7.9, 5.4, 6.4, and 2.1, respectively, for magnetite (Tombacz et al 2006), hematite (Huang et al 2001), pyrite (Borah and Senapati 2006), and quartz (Kroutil et al 2015). In this study, the pzc values of the PA were determined to be 4.6.…”
Section: Resultsmentioning
confidence: 99%